Consensus on a jockey's injury prevention framework for video analysis: a modified Delphi study. Issue 4 (15th December 2022) - Lucas, Daloni; Stokes, Keith; McGuigan, Polly; Hill, Jerry; Cazzola, Dario
Abstract : Professional horse racing is a high-risk and dangerous sport with a high incidence of falls and injuries. While falls in horse racing are considered somewhat inevitable and carry an inherent occupational risk, little is known about the actual mechanisms of jockey injuries. Establishing injury aetiology and mechanism is a fundamental step in informing the design and implementation of future injury prevention strategies. Despite the availability of horse racing video footage, the use of video analysis to examine injury mechanisms is an underused practice. Using an expert consensus-based approach, an industry expert steering committee was assembled to develop a framework for video analysis research in horse racing. The aim of the framework is to encourage and facilitate the use of video analysis in the sport and to ensure consistency and quality of future application. To achieve consensus, a systematic review and modified Delphi method study design was used. Responses of the steering committee to two open-ended questions regarding the risk factors of falls and injury were collated and combined with findings from a literature search strategy. Appropriate descriptors and definitions were then formulated that defined and described key features of a jockey fall in horse racing and grouped into six discrete phases of an inciting event. Each member of the steering committee then examined the framework of proposed descriptors and definitions and rated their level of agreement on the 5-point Likert scale. A consensus was achieved on a total of 73 horse racing-specific descriptors and 268 associated definitions. The framework outlined in this study provides a valuable starting point for further research and practice within this area, while the recommendations and implications documented aim to facilitate the practical application of video analysis in horse racing.